IDENTIFICATION OF JUVENILES OF THREE SPECIES OF METAPENAEUS (DECAPODA, PENAEIDAE) - Rao, P Vedavyasa (Indian Journal of Fisheries, 2011)
Distinguishing characters of juveniles (10 to 27 mm body length) of three species of commercially important prawns, namely, Metapenaeus dobsoni, M. nionoceros and M. affinis are described. Colouration of body, distribution pattern of chromatophores on carapace and abdominal segments, and length of rostrum of each of the species are compared. A key for their identification is provided based on these characters.